2016
DOI: 10.1038/nrneph.2016.85
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of disease states in kidney transplant biopsy samples

Abstract: Progress in renal transplantation requires improved understanding and assessment of rejection and injury. Study of the relationship between gene expression and clinical phenotypes in kidney transplant biopsy samples has led to the development of a system that enables diagnoses of specific disease states on the basis of messenger RNA levels in the biopsy sample. Using this system we have defined the molecular landscape of T cell-mediated rejection (TCMR), antibody-mediated rejection (ABMR), acute kidney injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
141
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 112 publications
(128 reference statements)
2
141
0
2
Order By: Relevance
“…In contrast, there is considerable heterogeneity among published studies with regard to how the molecular phenotype has been assessed and applied as a potential diagnostic and/or predictive tool 46. Over the last decade, transplant biopsies, blood, and urine have been studied comprehensively, primarily using transcriptomics, and have led to novel insights into the molecular phenotypes of organ transplants 47, 48, 49, 50, 51, 52, 53. Current ongoing studies—for example, the INTERCOM studies 47, 48—are assessing a molecular microscope approach in real time for examining kidney allograft biopsies and comparing the gene expression classifiers and diagnosis to the current gold standard histopathology.…”
Section: Prospects For Adopting Molecular Pathology In Renal Allografmentioning
confidence: 99%
“…In contrast, there is considerable heterogeneity among published studies with regard to how the molecular phenotype has been assessed and applied as a potential diagnostic and/or predictive tool 46. Over the last decade, transplant biopsies, blood, and urine have been studied comprehensively, primarily using transcriptomics, and have led to novel insights into the molecular phenotypes of organ transplants 47, 48, 49, 50, 51, 52, 53. Current ongoing studies—for example, the INTERCOM studies 47, 48—are assessing a molecular microscope approach in real time for examining kidney allograft biopsies and comparing the gene expression classifiers and diagnosis to the current gold standard histopathology.…”
Section: Prospects For Adopting Molecular Pathology In Renal Allografmentioning
confidence: 99%
“…Our previous studies have been based on such classifiers comparing rejection vs. nonrejection phenotypes (10)(11)(12)(13)(14). However, we have subsequently found that methods that combine multiple classifiers provide better estimates than single classifiers (15), implying that a new method is needed to assemble the input from multiple classifiers into a single probabilistic assessment. (27), only MMF (5), no IS treatment (244).…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a system for translating gene expression measurements into diagnostic assessment: the molecular microscope diagnostic system (MMDx) (1). Like histology, a molecular biopsy assessment system requires consideration of the effect of sample adequacy.…”
Section: Introductionmentioning
confidence: 99%